Effect of Dietary Natural Capsaicin on Experimental Salmonella enteritidis Infection and Yolk Pigmentation in Laying Hens - Vicente, J.L.; Lopez, C.; Avila, E.; Morales, E.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2007)
This study evaluated capsaicin extracted from chili pepper and its prophylactic effect on Salmonella enteritidis (SE) experimental infection, feed conversion, egg production, egg weight and yolk pigmentation in laying hens. Dekalb hens (30/treatment) were fed for 28 days with two different levels (18 and 36 ppm) of dietary capsaicin from paprika oil. Both levels (18 and 36 ppm) of dietary capsaicin did not affect the feed conversion, egg production or egg weight. At 25 days, hens were challenged with 108 cfu mL-1 of SE. Three days after inoculation, liver and spleen were collected aseptically and cultured as a combined sample. The higher capsaicin treatment significantly decreased (p<0.05) SE organ invasion (43.44%; 13/30) when it was compared with the low capsaicin treatment (56.67%; 17/30) and control group (76.67%; 23/30). Eggs were collected on day 20 of the trial and the yolk pigmentation was measured directly with a chroma meter CR-300 (Minolta) in the CIELab scale. Both concentrations of dietary capsaicin significantly increased the deposition of red pigment on egg yolk (14.11±1.40 and 17.44±1.90) compared with control group (-1.58±2.65). The results of the present investigation suggest that the natural capsaicin, extracted from paprika seeds at 36 ppm in the diet, had a prophylactic effect on experimental SE infection in laying hens and both concentrations of capsaicin increased red pigmentation of the yolk.